Bryllup, mening og moral - Blehr, Barbro (Tidsskrift for kulturforskning, 2003)
Royal weddings are magical moments. By stirring emotions and moving the public, they may redirect opinion and silence critical voices - at least for a while. This paper argues that a more long-term support for the monarchy will need an additional underpinning of respect for royal professionalism, and that studies of royal weddings, accordingly, should pay attention to how these ceremonies present their main characters as professional royal performers. The point is exemplified by a tentative comparison of the weddings of the Norwegian Crown Prince, in August, 2001 and a Norwegian princess, in May, 2002, and by some reflections on public reactions to these weddings.